Local probing of magnetoelectric properties of PVDF/Fe3O4 electrospun nanofibers by piezoresponse force microscope - Zheng, Tian (2017)
The coupling of magnetic and electric properties in magnetoelectric polymer-based composites offers new opportunities to develop contactless electrodes, effectively without electrical connections, for less-invasive integration into devices such as energy harvesters, sensors, wearable and implantable electrodes. Understanding the macroscale-to-nanoscale conversion of the properties is important, as nanostructured and nanoscale magnetoelectric structures are increasingly fabricated. However, whilst the magnetoelectric effect at the macroscale is well established both theoretically and experimentally, it remains unclear how this effect translates to the nanoscale, or vice versa. Here, PVDF/Fe3O4 polymer-based composite nanofibers are fabricated using electrospinning to investigate their piezoelectric and magnetoelectric properties at the single nanofiber level.